Binding the Islands Air Transport and State Capacity Building in the Philippines, 1946 to 1961 - Mendoza, Meynardo P. (Archīum Ateneo, 2013)
State capacity building, which became very pronounced in the immediate postwar period, saw the development of air transport. The relationship between the state and Philippine Airlines (PAL) was mostly symbiotic. The state infused huge investments in the airline, absorbed its losses, and protected it from competition as well as congressional inquiries on the use of scarce public resources in a private company. In return, the airline had to fly to very remote areas, not so much to ferry paying passengers as to link these areas to the center by bringing in mail, medicines, newspapers, and even government personnel and equipment.